DEVELOPMENT OF CELL-PENETRATING NANOPARTICLES FOR DRUG DELIVERY - Zhaisanbayeva, Balnur (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Recently, there has been a growing interest in nanoparticle-related pharmaceutical and biomedical research. Anticipated outcomes of such applications include the development of in vitro and in vivo diagnostics kits, improved biocompatible materials production, and advancing drug delivery systems. In the realm of inorganic nanoparticles, silica or materials coated with silica exhibit potential for biomedical applications due to their small size, stable chemical structure, colloidal stability, and high surface reactivity. Despite the growing interest in silica nanoparticles, little is known about their toxicity resulting from the various synthesis methods; thus, recent findings often contradict each other. Moreover, most synthesis studies need more information about nanoparticle behaviour in the physiological environment, making it challenging to understand the biological effects of these nanoparticles for further clinical trials. Therefore, a newly emerging approach, safe-by-design, is starting to play a crucial role in developing nanoparticles for biomedical sciences. This dissertation explores organosilica nanoparticles synthesised from 3-mercaptopropyltrimethoxysilane (MPTS) for potential biomedical applications as a drug delivery system. The work involves extensive characterisation and toxicological evaluation of organosilica nanoparticles with thiol groups on the surface. The experiments have underscored the safety of organosilica nanoparticles through comprehensive in vitro and in vivo assessments. The further potential use of these nanoparticles was explored by covalently attaching cell-penetrating peptide (TAT) and anticancer drugs (doxorubicin). The findings of this work demonstrated that the functionalised nanoparticles changed the function of thiolated nanoparticles, and conjugated drugs continued to be effective and retain their properties.
Keywords: type of access: open access; nanoparticles; drug delivery